2018
DOI: 10.1136/bmjresp-2018-000304
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis and the influence of surveillance strategy on tuberculosis case-finding and all-cause mortality: a cluster randomised trial in Indian neonates vaccinated with BCG

Abstract: IntroductionAccurate tuberculosis (TB) incidence and optimal surveillance strategies are pertinent to TB vaccine trial design. Infants are a targeted population for new TB vaccines, but data from India, with the highest global burden of TB cases, is limited.MethodsIn a population-based prospective trial conducted between November 2006 and July 2008, BCG-vaccinated neonates in South India were enrolled and cluster-randomised to active or passive surveillance. We assessed the influence of surveillance strategy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…in the same study area reported a birthweight of ≤2500g in 29% of 4382 neonates(44) which taken together suggests an explanation for the low BCG scar rate in the present study. Surprisingly, neither the TB exposure scores or other well-established TB risk factors had a clear association with incipient TB in multivariate analysis.…”
supporting
confidence: 76%
“…in the same study area reported a birthweight of ≤2500g in 29% of 4382 neonates(44) which taken together suggests an explanation for the low BCG scar rate in the present study. Surprisingly, neither the TB exposure scores or other well-established TB risk factors had a clear association with incipient TB in multivariate analysis.…”
supporting
confidence: 76%
“…However, these require large sample sizes, long term follow-up and are resource intensive. We only identified three RCTs, conducted over relatively short time-periods (1-2 years) [28,36,37]. Therefore, insights from routine programme implementation are essential.…”
Section: Discussionmentioning
confidence: 99%
“…From 27,270 articles, 18 were eligible [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Figure 1 and Table 2); seven were not reported in the previous review [20,[29][30][31][32]36,37]. We only identified n=12/23 (52%) of the outcome indicators sought (Table 1); no studies reported on the remainder.…”
Section: Clinical Reviewmentioning
confidence: 99%
See 2 more Smart Citations